Current source implementations for fundamental SS2-FDTD method - Gan, Theng Huat (2013)
This paper presents the current source implementations for the fundamental second-order accurate split-step unite-difference time-domain (SS2-FDTD) method. To improve efficiency, the SS2-FDTD method is formulated in the most fundamental form with the simplest and most concise right-hand sides free of matrix operators. The consistent and symmetrical current source implementations of the two-substep alternating-direction-implicit (ADI) FDTD method are extended and investigated for the three-substep SS2-FDTD method. Numerical results are presented to compare various current source implementations for the fundamental SS2-FDTD method.